Differences in reaction force-time characteristics experienced by females when running on a track at different speeds - Steward, H. E.; McNitt-Gray, J. L. (ISBS Proceedings Archive (Michigan), 2020)
Elite collegiate runners are susceptible to sustaining lower extremity stress related injuries. Ground reaction forces (GRFs) were analyzed to understand differences in mechanical loading at steady state 5.5 and 7 min/mile paces. We hypothesized GRF magnitudes would increase with speed while horizontal GRFs during braking would be unique to each participant. GRFs, inertial measurement units, and high speed video were collected during outdoor over ground running. Group differences were observed that were not always significant within participant. As speed increased, average horizontal GRF during braking (-0.25 to -0.29 BWs) decreased while peak vertical GRF increased (2.75 to 2.91 BWs). The unique pattern of the sagittal plane resultant GRF orientation was maintained during initial braking phase which may indicate this orientation is a nervous system control priority.